Argon effect on thermal expansion of fullerite C60 - Aleksandrovskii, A. N.; Gavrilko, V. G.; Esel`son, V. B.; Manzhelii, V. G.; Udovidchenko, B. G.; Maletskiy, V. P.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The linear thermal expansion of compacted Ar-doped fullerite C60(ArxC60) is investigated at 2-12 K using dilatometric method. The thermal expansion of ArxC60 was also studied after partial desaturation of argon from fullerite. It is revealed that argon doping resulted in the considerable change of thetemperature dependence of the thermal expansion of fullerite. An explanation of the observed effects is proposed.